PENGARUH KURS DAN SUKU BUNGA SBI SERTA INFLASI MELALUI RETURN ON ASSET TERHADAP RETURN SAHAM - Alfiatul Maulida (STIE Mandala Jember, 2016)
This study uses secondary data from the Indonesia Stock Exchange on eachof the companies in the Stock Exchange with the period 2010-2014 and the researchusing quantitative research methods. The location used to do research is to take datadirectly from the Internet. Sampling using purposive sampling method and gained asmuch as 9 companies as research samples. The analytical method used is pathanalysis. The results showed a variable rate significant negative effect on the returnon assets. The variable interest rate of SBI and inflation is not significant positiveeffect on return on assets. Variable rate significant negative effect on stock returns.Variable interest rates SBI significant positive effect on stock returns. Inflationvariable is not significant positive effect on stock returns. While the indirect teststates that a variable rate, SBI interest rate and inflation through the return on assetson stock returns no significant effect.